Effect of ionic liquid structure on viscoelastic behavior of hydrogen-bonded micellar ion gels. (12th September 2019) - Tamate, Ryota; Hashimoto, Kei; Li, Xiang; Shibayama, Mitsuhiro; Watanabe, Masayoshi
Abstract: Ion gels based on block copolymer self-assembly in ionic liquids (ILs) are attractive, processable, non-volatile, ion-conducting soft materials. Recently, a new class of ion gels based on hydrogen bonding between jammed block copolymer micelles in ILs that shows good mechanical strength and rapid self-healing ability has been developed. Herein, the effect of IL cation and anion structures on the microstructures and viscoelastic properties of a hydrogen-bonded micellar ion gel is reported. It was clarified that competition among cations, anions, and polymer chains for hydrogen bonding significantly affects the viscoelastic behavior of the ion gel. In the case of weak hydrogen bonding for ILs, macroscopic phase separation occurs due to strong hydrogen bonding between diblock copolymer micelles, resulting in an opaque and fragile ion gel, whereas storage and loss moduli are significantly reduced for ILs showing strong hydrogen bonding. Control of competitive hydrogen bonding interaction between polymers and ILs is thus critical to obtaining the desirable physical properties for ion gels. Graphical abstract: Image 1 Highlights: Hydrogen-bonded micellar ion gels with different IL structures are fabricated. Viscoelastic properties significantly depend on the IL cation/anion structure. Competitive hydrogen-bond between ILs and polymers is crucial for viscoelasticity. ILs having strong hydrogen bond ability suppress the intermicellar interaction. Tuning of the competitive interaction is a key to achieve desirable properties.